Variation in UK Deanery publication rates in the British Journal of Oral and Maxillofacial Surgery: where are the current 'hot spots'?. Issue 2 (February 2021) - Turner, J.; Hammond, D.; Goodson, M.
Abstract: Publication in peer-reviewed journals is often seen as a cornerstone of the academic and clinical career within medicine and surgery. As one of the largest circulations in oral and maxillofacial surgery, the British Journal of Oral and Maxillofacial Surgery (BJOMS) offers trainees and consultants the opportunity to disseminate valuable information worldwide. The aim of this paper is to investigate the variation in publication rates of U.K. authors based upon their Deanery in order to identify potential hotspots. All volumes of BJOMS between 2011 and 2019 were hand searched to identify full articles authored by authors in U.K., these were categorised by Deanery and allocated a theme within OMFS. The results demonstrate that, of the 378 full length articles, over 30% of these were from two Deaneries: London and North West (West). Oncology, OMFS training and education, and craniofacial trauma were the three most common themes of publication amounting to 51.5% of total publications. There has been an unfortunate decrease in publications from U.K. Deaneries of almost 30% from 2011 to 2019 which begs the question of whether fewer publications are being accepted or if rates of submission have reduced.